Biodegradation of Poly (3-hydroxybutyrate) /Eggshellsystems - Sá,Marcel Leiner de (2018)
In this work, biocomposites of poly (3-hydroxybutyrate) (PHB) / calcium carbonate from Rhea Americana eggshells were prepared and the effects of the addition of the inorganic filler in the polymeric matrix were assessed. The residue (powder) of the eggshell calcined at 400 ºC or in natura was inserted into a PHB solution for preparation of films via casting. Powder samples were characterized by X-Ray Fluorescence (XRF), X-Ray diffraction (XRD) and Thermogravimetry (TG/DTG) and films were characterized by X-Ray diffraction (XRD), Scanning Electron Microscopy (SEM) and biodegradation tests according to the ASTM G 160-03 norm: the results were reported as weight loss and visual inspection by optical microscopy (OM). From the results of the XDR, it was perceived that the peaks in the diffractograms of the powder obtained by milling the Rhea Americana eggshells corresponded to the diffraction patterns of the Calcite crystals, which is a calcium carbonate polyform, and that the calcination preserved the crystalline structure, maintaining the calcium carbonate in the samples. For the biocomposites, a peak characteristic to the calcium carbonate in 29.57º was detected, indicating the insertion of the filler to the polymer matrix. Through SEM the presence of small agglomerates, probably due to polymer particles that were not dissolved, was observed for the pure PHB film. With the addition of the filler in natura a greater porosity was formed in the surface of the biocomposite films, and with the calcined filler, homogeneous films with reduced porosity were obtained. From the weight loss and OM results, it was observed that the filler inserted into the polymeric matrix catalyzes the biodegradation process up to 60 days evaluation in different ways, depending on the type of sample used.